Molecular characterization of hepatitis C virus genotype 4 sequences in HIV-coinfected patients from Argentina - Bolcic, Federico Martin (2011)
The prevalence of hepatitis C virus genotype 4 (HCV-4) is increasing in different parts of the World but in Latin America the data are still scarce. We aimed to characterize HCV-4 isolates from 383 HIV-coinfected patients in Argentina. Sequence analyses were based on the non-structural 5B region of HCV. Results from 18 patients indicated a genetic heterogeneity that involved three genotype 4 subtypes. Sequences were ascribed to subtype 4d (67%), 4a (22%) and 4m (11%). In spite of different sources of transmission were defined among patients, no statistical association was found with the genotype 4 subtype. The scenario is also compatible with multiple importation of the epidemic and there is no evidence for transmission–specific clusters or network-like transmission of HCV-4. This HCV-4 does not represent a recent introduction in Argentina, it circulates in all transmission groups and its presence is increasing among HIV-infected patients.